A Review on Biodiesel Production through Heterogeneous Catalysis Route. Issue 4 (2nd August 2018) - Sahu, Gajanan; Gupta, Navneet Kumar; Kotha, Akhil; Saha, Sujan; Datta, Sudipta; Chavan, Prakash; Kumari, Neelam; Dutta, Pashupati
Abstract: Depletion of oil reserves, increasing prices of petroleum products, and environmental concerns related to air pollution are the main driving forces for utilizing renewable energy resources to replace fossil fuels. Vegetable oils can be used to produce biodiesel. Biodiesel is obtained by transesterification of vegetable oil with alcohol using homogeneous or heterogeneous catalysts. In the industry, biodiesel is produced by heterogeneous catalysts due to high activity and selectivity, better reusability, reduction in processing steps, and wastes. The catalytic activity of catalysts depends on the strength and type of intrinsic basic or/and acid properties. Biodiesel production using heterogenous catalysts depends on the various reaction parameters such as reaction time, temperature, molar ratio of alcohol to oil, catalyst amount, and stirring speed. In this paper, the catalytic transesterification of various feedstocks such as edible oil, non‐edible oil, and waste using heterogeneous catalysts has been reviewed and optimization parameters for maximum biodiesel production have been summarized. Abstract : Biodiesel is an alternative for petroleum diesel fuel which can be used in internal combustion and other engines. It is synthesized from fat/oil by transesterification in the presence of alcohol and a suitable catalyst. Issues related to the role of the catalyst, acid‐base properties, different oils/fats and alcohols, reaction parameters, and their effects on catalytic activity, selectivity, and catalyst lifetime have been critically discussed.